Influence of probiotic supplementation on climacteric symptoms in menopausal women-A mini review - Bhagavathi Sundaram Sivamaruthi (2018)
© 2018 The Authors. Menopause (MP) is a natural physiological event of woman’s life and is defined as the absence of menstrual periods for at least twelve months and loss of function of ovarian. The common symptoms of MP are irregular vaginal bleeding, hot flushes especially in head and chest, night sweats, insomnia, vaginal and urinary symptoms, cognitive dysfunction, increased cancer risk, osteopenia, high blood pressure, diabetes, and cardiovascular diseases. Microbiome has been associated with several health benefits. Probiotic supplementation helps to enhance the quality of microbiome thereby confers the health benefits to the host system. The microbiome, hormone (estrogen) changes, and probiotic intervention are related to the health status of the female reproductive system. The vaginal microbiome (VM) play a critical role in female reproductive health and MP, which can be greatly influenced by probiotics, and other medicine especially antibiotics and hormone therapy. The role of VM in supporting vaginal health is not clear and debatable. Understanding the role of vaginal Lactobacillus could expose the pathogenesis of vaginal dysbiosis, which helps to improve diagnostic and therapeutic strategies for several dysbiosis associated health issues and menopause-related symptoms. Recent studies suggested that the intervention of probiotic preparation with or without nutraceutical formulation (mostly with isoflavones) improve the health status of menopausal women. The mechanism of probiotics mediated health improvement in menopausal women is not yet described clearly. Several controversies are there on the link between probiotic, gut microbiota, vaginal microbiota, and estrogen deficit. The present review summarizes the influence of probiotic supplementation on climacteric symptoms in menopausal women. The literature search was made in Scopus, Google Scholar, PubMed using the keywords “probiotics” and “menopause”. The documents were carefully checked for the relevance to the current manuscript, and the selection was made without any restriction in the year of publication.